1995
DOI: 10.1177/027112149501500402
|View full text |Cite
|
Sign up to set email alerts
|

Weaving Interventions into the Fabric of Everyday Life

Abstract: In response to legislative mandates, the focus in early childhood special education has shifted from the child to the child in the context of the family. This shift has major implications for assessment as well as for intervention. In this article we describe an ecocultural approach for assessing families of young children with developmental problems. It is an approach that has grown out of empirical work and that we believe has clinical utility in designing interventions for young children and their families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
63
0
4

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(67 citation statements)
references
References 24 publications
0
63
0
4
Order By: Relevance
“…The family member's cultural and educational background, view of professionals as partners, and current status of emotional or physical health are factors that can impact responsiveness to questions or comments from a service provider. The information gathered in an interview or a conversation will not only vary by the method employed but also be related to the variability of the family's lives (Bernheimer & Keogh, 1995;Bernheimer & Weismer, 2007).…”
Section: Moving the Interview To A Conversationmentioning
confidence: 99%
“…The family member's cultural and educational background, view of professionals as partners, and current status of emotional or physical health are factors that can impact responsiveness to questions or comments from a service provider. The information gathered in an interview or a conversation will not only vary by the method employed but also be related to the variability of the family's lives (Bernheimer & Keogh, 1995;Bernheimer & Weismer, 2007).…”
Section: Moving the Interview To A Conversationmentioning
confidence: 99%
“…Assim, os ambientes naturais de aprendizagem do dia-a-dia, as experiências e oportunidades normalizadoras, bem como o envolvimento activo e co-responsabilização da família, constituem ingredientes fundamentais do pensamento actual sobre como conseguir tais benefícios (Dunst, Raab, Trivette, & Swanson, 2010). Nesta perspectiva, as rotinas da família passaram a ter uma relevância fundamental em IP, acompanhando as mudanças paradigmáticas de uma intervenção centrada na criança para uma intervenção centrada na família (Bernheimer & Keogh, 1995). As práticas de IP embutidas nas rotinas são congruentes com a prestação de ajuda centrada na família (Dunst, Hamby, Trivette, Raab, & Bruder, 2002).…”
Section: Bases Conceptuais Das Práticas De Ip Baseadas Nas Rotinasunclassified
“…When parents correctly practiced goals with their infant/toddler, child developmental outcomes improved. When goals were aligned with family culture and parent priorities, parents were more likely to meet the intensive practice schedule required for maximum gains and promotion of generalization of new skills in infants/toddlers with disabilities (Bernheimer & Keogh, 1995). Best practices in EI research repeatedly demonstrated that with collaborative support, parent involvement increased intervention effects (Ketelaar, Vermeer, Helders, & Hart, 1998;Shonkoff & Hauser-Cram, 1987).…”
Section: Section Summarymentioning
confidence: 99%